2009
DOI: 10.2337/dc09-0552
|View full text |Cite
|
Sign up to set email alerts
|

Troponin T and Pro–B-Type Natriuretic Peptide in Fetuses of Type 1 Diabetic Mothers

Abstract: OBJECTIVECardiomyopathy is noted in up to 40% of infants of diabetic mothers, and the exact mechanisms are unknown. The aim of this study was to determine whether fetal serum markers of cardiac function differ between normal and type 1 diabetic pregnancies and to examine the relationship between these markers and fetal cardiac structure and function.RESEARCH DESIGN AND METHODSThis was a prospective observational study of 45 type 1 diabetic pregnancies and 39 normal pregnancies. All participants had concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 28 publications
(39 reference statements)
3
37
0
Order By: Relevance
“…However, another study of the same group evaluated the correlation between umbilical artery troponin T and proBNP levels at the time of delivery and third trimester cardiac structure and function parameters of pregestational IDMs. The study found a correlation between proBNP level and IVS thickness; however, no such correlation was found with troponin T level [17]. Similarly, in our study, we found a positive correlation between the NT proBNP level and interventricular septum thickness in pregestational and gestational IDMs.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…However, another study of the same group evaluated the correlation between umbilical artery troponin T and proBNP levels at the time of delivery and third trimester cardiac structure and function parameters of pregestational IDMs. The study found a correlation between proBNP level and IVS thickness; however, no such correlation was found with troponin T level [17]. Similarly, in our study, we found a positive correlation between the NT proBNP level and interventricular septum thickness in pregestational and gestational IDMs.…”
Section: Discussionsupporting
confidence: 60%
“…The literature is mainly limited to infants of pregestational (type 1) diabetic mothers [9,12,17]. A study on the infants of pregestational diabetic mothers showed that umbilical cord plasma proBNP levels were significantly higher than those of the control group [12,17].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This together with the presence of positive correlation with the indicators of the cardiac diastolic and systolic dysfunction imply the value of cord blood cardiac troponin-T as an indicator of the cardiac injury associated with diabetes during pregnancy. Russell, et al [34] found higher concentration of cardiac troponin-T in the diabetic cohort than in the normal cohort and found higher concentration of cardiac troponin-T in infants of diabetic mothers, especially those with cardiomyopathy and those with poor perinatal outcome [34]. Tarkowska & Furmaga-Jabłońska [35] found significantly higher cardiac troponin-T levels in newborns with heart pathology than in healthy ones [35].…”
Section: /9mentioning
confidence: 99%
“…Classically, chronic hypoxia, hyperglycaemia and lactic acidosis are thought to contribute to the risk of intrauterine death but placental function may also play a part. Even well controlled pre-gestational diabetic mothers with normally grown fetuses have an increased risk of perinatal mortality and morbidity, including fetal cardiomyopathy and late third trimester unexplained fetal death [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%